"The Role of Sustainable Performance in SMEs: Bibliometric Analysis and Future Research" - Ramadhan, Agil Mumtaz; Hanoum, Syarifa; Arif Handiwibowo, Gogor (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In an increasingly competitive business era, the SME sector faces challenges in maintaining sustainable performance, including in social, economic, and environmental aspects. This study was conducted to explore how research on this topic develops in the scientific literature and to identify collaboration patterns among authors and academic institutions. This study used bibliometric analysis from the Scopus database combined with content analysis of the most influential publications. The results show an increase in the number of publications related to sustainable performance in SMEs in recent years. Several key themes that frequently emerge in this research include sustainable business strategies in enhancing SME competitiveness. Furthermore, a collaborative network analysis indicates that research in this field is still dominated by certain institutions and academic groups. This study confirms that sustainable performance is a crucial aspect for the sustainability of SMEs amidst global challenges. These findings provide insights for academics and practitioners to develop more effective sustainability strategies.